Effect of Vitamin E on Indomethacin Induced Gastropathy in Mice - AyeshaYousaf ,ShaistaAli ,IfraSaeed (Journal of Rawalpindi Medical College, 2018)
Background:To evaluate the effect of indomethacin on gastric mucosa of mice and to study the effect of Vitamin E on Indomethacin treated gastric mucosa. Methods: In this experimental study 48 adult male mice were randomly divided into four groups ,comprising of 12 mice each. Group A was labelled as the control group. Evion 400mg/kg was given to group B. Indocid 25mg/kg was administered to group C. Combination of Indocid and Evion (25mg/kg & 400 mg/kg respectively) was given to group D. Dose was administered for three days to 6 mice of each group and for eight days to other 6 mice. Their body weights at the beginning and end of experiment were noted. Stomach was dissected, washed and fixed. The histological parameters observed were epithelial integrity and haemorrhage. Results: In group A and B findings were normal. Weight of animals in group C was significantly decreased as compared to group D (p-value<0.05). Disturbed integrity of gastric mucosa and haemorrhages were seen in group C. Conclusion: Indomethacin produced gastric ulcers were decreased by giving Vitamin E in mice.